2022
DOI: 10.21037/tlcr-22-611
|View full text |Cite
|
Sign up to set email alerts
|

Value of 18-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) in the differential diagnosis of sarcoidosis and lung cancer with lymph node metastasis: a retrospective study

Abstract: Background: Fluorine 18-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) has been proven to be valuable in guiding the diagnosis and management of sarcoidosis.However, its differential value for sarcoidosis is unclear. The objective of this study was to explore the value of 18F-FDG PET/CT in differentiation sarcoidosis from lung cancer with lymph node metastasis.Methods: A total of 361 consecutively diagnosed sarcoidosis patients and 1,944 consecutively diagnosed lung cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…To avoid overfitting, the model was given an additional drop layer, but the model still underperformed. This can be attributed to the need for deep learning models to have a large number of high-quality images, and medical images, especially PET/CT images, being more difficult to obtain, more expensive to annotate, and more time consuming than other imaging disciplines ( 37 , 38 ). Despite attempts to increase the sample size and improve deep learning model classification accuracy through migration learning ( 39 ) and data augmentation ( 40 ), the results remain unsatisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid overfitting, the model was given an additional drop layer, but the model still underperformed. This can be attributed to the need for deep learning models to have a large number of high-quality images, and medical images, especially PET/CT images, being more difficult to obtain, more expensive to annotate, and more time consuming than other imaging disciplines ( 37 , 38 ). Despite attempts to increase the sample size and improve deep learning model classification accuracy through migration learning ( 39 ) and data augmentation ( 40 ), the results remain unsatisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of exposure to silica and beryllium or drug intake made it possible not to retain the toxic or drug causes. In case of doubt between sarcoidosis and a malignant tumor, positron emission tomography is a useful examination but its routine use is not yet unanimous [19]. Therapeutically, abstention is recommended in cases of asymptomatic stage 1 or 2 lung involvement [3,20].…”
Section: Discussionmentioning
confidence: 99%
“…18 F-FDG PET-CT is widely used for the diagnosis, staging and therapeutic assessment of malignancies and inflammatory diseases. It can reveal the anatomical localization of residual FDG uptake throughout the whole body, providing guidance for further diagnostic tests (28,29). Previous studies have demonstrated the good diagnostic performance of 18 F-FDG PET-CT for several inflammatory and infectious diseases, including fever of unknown origin and inflammation of unknown origin (30,31).…”
Section: Discussionmentioning
confidence: 99%